Comparison of the Effect of Adding Different Levels of Zinc Chloride, Curcumin, Zinc Oxide Nanoparticles (Zano‐NPs), Curcumin Loaded on Zano‐NPs on Post‐Thawing Quality of Ram Semen - Fatemeh Omidi; Hadi Hajarian; Hamed Karamishabankareh; Leila Soltani; Mojtaba Dashtizad (Veterinary Medicine and Science)
ABSTRACT Objective This study looked at how different concentrations of curcumin (Curc), zinc chloride (ZnCl2), zinc oxide nanoparticles (ZnO‐NPs) and Curc loaded on ZnO‐NPs (Curc‐co‐ZnO‐NPs) in cryopreservation dilution affected the quality of ram sperm after thawing. Methods ZnO‐NPs were synthesised using Berberis vulgaris leaf aqueous extract. Then, Curc was loaded on the ZnO‐NPs that had been synthesised. We used analytical methods to look at the composition, morphology and size of green synthesised ZnO‐NPs and Curc‐co‐ZnO‐NPs, including UV‐Vis, zeta potential, EDX, DLS, FE‐SEM and FT‐IR. Using a Tris‐base extender containing various concentrations of Curc, ZnCl2, ZnO‐NPs and Curc‐co‐ZnO‐NPs (0, 1, 10 and 100 µg/mL), semen samples from four rams were combined. Sperm motility, viability, DNA and plasma membrane integrity, total abnormalities and malondialdehyde (MDA) generation were all evaluated in treatment groups after thawing. Results The results showed that adding 1 µg/mL of ZnO‐NPs and Curc‐co‐ZnO‐NPs significantly reduced the level of MDA and total abnormalities (p < 0.05). Additionally, following the freeze‐thawing procedure, the presence of 1 µg/mL of Curc‐co‐ZnO‐NPs in the diluent of ram sperm significantly increased the percentage of sperm viability and motility in comparison to the control and other treatment groups (p < 0.05). Furthermore, as compared to the control group and other treatments, treatments containing 1 µg/mL of Curc‐co‐ZnO‐NPs significantly improved membrane and DNA integrity (p < 0.05). Conclusions It appears that following freeze‐thawing, the Curc‐co‐ZnO‐NPs (1 µg/mL) enhanced sperm parameters.